Effects of different wheat bran fermentation sources on growth performance, nutrient digestibility, serum antioxidant capacity and fecal microbiota in growing pigs - Liu, Heng; Ren, Xiaojie; Li, Yang; Cao, Qingjie; Yang, Lijie; Jiang, Shuzhen; Fu, Jiawei; Gao, Jie; Yan, Lei; Li, Junxun; Yang, Weiren (Frontiers in Veterinary Science, 2023)
The present study aimed to evaluate the application of different wheat bran fermentation sources in growing pigs. A total of 320 pigs (43 ± 0.21 kg), were randomly allocated to 5 groups in a 21-d trial. The control group was fed a basal diet (CON) containing raw wheat bran, and the other four treatments were fed the diets in which the raw wheat bran in the basal diet was substituted with Aspergillus niger (WBA), Bacillus licheniformis (WBB), Candida utilis (WBC), and Lactobacillus plantarum (WBL) fermented wheat bran, respectively. The results showed that compared to the CON group, the crude fiber and pH values were decreased (P < 0.05), while the gross energy (GE), crude protein (CP), and lactic acid values were increased (P < 0.05) in all the wheat bran fermented by different strains. Compared with other treatments, feeding B. licheniformis fermented wheat bran had higher final weight, average daily gain, as well as lower feed-to-gain ratio. Compared with CON group, pigs fed with fermented wheat bran diets had higher dry matter, CP, and GE availability, serum total protein, albumin and superoxide dismutase levels, and fecal Lactobacillus counts, as well as lower malondialdehyde level and fecal Escherichia coli count. Collectively, our findings suggested that feeding fermented wheat bran, especially B. licheniformis fermented wheat bran, showed beneficial effects on the growth performance, nutrient digestibility, serum antioxidant capacity, and the gut microbiota structure of growing pigs.